A systematic review of case-mix models for home health care payment: Making sense of variation. Issue 2 (February 2020) - van den Bulck, Anne O.E.; de Korte, Maud H.; Elissen, Arianne M.J.; Metzelthin, Silke F.; Mikkers, Misja C.; Ruwaard, Dirk
Highlights: Different case-mix models exist for prospective home health care (HHC) payment. These models explain 14%–54.3% of variance in HHC utilization/costs. There is a considerable variation in included case-mix predictors across models. Common predictors relate to physical functioning, daily functioning, and health service use. Few of the identified case-mix models are implemented in HHC practice. Abstract: Background: Case-mix based payment of health care services offers potential to contain expenditure growth and simultaneously support needs-based care provision. However, limited evidence exists on its application in home health care (HHC). Therefore, this study aimed to synthesize available international literature on existing case-mix models for HHC payment. Methods: We performed a systematic review of scientific literature, supplemented with grey literature. We searched for literature using six scientific databases, reference lists, expert consultation, and targeted websites. Data on study design, case-mix model attributes, and conclusions were extracted narratively. Results: Of 3303 references found, 22 scientific studies and 27 grey documents met eligibility criteria. Eight case-mix models for HHC were identified, from the US, Canada, New Zealand, Australia, and Germany. Three countries have implemented a case-mix model as part of a HHC payment system. Different combinations of in total 127 unique case-mix predictors are included across models to predict HHC use. Case-mix models also differ in targeted services, operationalization, and outcome measures and predictive power. Conclusions: Case-mix based payment is not yet widely used within HHC. Multiple varieties were found between HHC case-mix models, and no one best form of a model seems to exist. Even though varieties are partly inevitable due to country-specific contexts, developing a shared vision in case-mix model attributes would be key to achieving efficient, needs-based HHC.